Improvement in the mechanical performance of Multi Jet Fusion–printed aramid fiber/polyamide 12 composites by fiber surface modification - Chen, Jiayao (2022)
Surface modification of reinforcement fibers is a potent strategy for enhancing the mechanical performance of fiber-reinfored composites. However, the strategy has rarely been applied to powder bed fusion because of the limited modification effectiveness. Here, a new surface modification method for aramid fibers (AFs) using amino-terminated hyperbranched polyamide (HBP) was proposed to improve the mechanical performance of the AF-reinforced polyamide 12 (PA12) composites printed by Multi Jet Fusion (MJF). The effect of the surface modification on the AFs was systematically examined by studying their surface morphology, chemical composition, and interfacial shear strength. The modified fibers were applied to fabricating PA12-based composite powders, which were then printed with an MJF printing testbed to reveal the effects of the fiber fraction, build orientation, and surface modification on their mechanical properties. The results showed that the surface modification of the AFs induced higher surface roughness by HBP coating and realized surface functionalization by amino groups. With the enhanced interfacial properties, the optimized AF-HBP/PA12 composite showed substantial improvement in its ultimate tensile strength and Young's modulus by 55% (73.4 MPa) and 110% (4.2 GPa), respectively, compared with the neat PA12 part. This simple and effective surface modification method can be further applied to other manufacturing technologies.